Development and validation of DNA markers linked to Sdvy-1, a common bean gene conferring resistance to the yellowing strain of Soybean dwarf virus - Yamashita, Yoko (Breeding science, 2014)
The yellowing strain of Soybean dwarf virus (SbDV-YS) causes yellowing and yield loss in common bean (Phaseolus vulgaris). The most effective control is achieved through breeding for resistance. An indeterminate climbing cultivar with a white seed coat, 'Oofuku', is resistant to SbDV-YS in inoculation tests. We crossed 'Oofuku' with an elite cultivar, 'Taisho-Kintoki', which is SbDV-YS-susceptible, determinate dwarf with a red-purple seed coat, and performed amplified-fragment-length polymorphism analysis of F3 lines. From nucleotide sequences of the resistant-specific fragments and their flanking regions, we developed five DNA markers, of which DV86, DV386, and DV398 were closely linked to Sdvy-1, a resistance gene. Using the markers, we developed 'Toiku-B79' and 'Toiku-B80', the near-isogenic lines (NILs) incorporating Sdvy-1 in the background of 'Taisho-Kintoki'. The NILs had similar growth habit, maturity date and seed shape to those of 'Taisho-Kintoki'. The quality of boiled beans was also similar, except that the NILs had more seed coat cracking than 'Taisho-Kintoki'. The NILs showed no SbDV-YS infection in inoculation tests. We suggest that Sdvy-1 is a useful source of SbDV-YS resistance in common bean